Odpowiedzi

2010-03-03T16:25:10+01:00
6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=-60+77-2
-15x=15
x=15:-15
x=-1


6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
-7,2x+17,5x-0,3x=6-21
10x=-15
x=-15:10
x=-1,5
1 5 1
2010-03-03T16:26:24+01:00
1. 6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=-60-2+77
-15x=15/:(-15)
x= -1

2. 6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
-7,2x+17,5x-0,3x=6-21
10x=-15/:10
x= -1,5
2010-03-03T16:29:48+01:00
1.
6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=77-2-60
-15x=15|:(-15)
x=-1

2.
6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
-7,2x+17,5x-0,3x=6-21
10x=-15|:10
x=-1,5